Une autre figure du community manager : un prospecteur silencieux et rigoureux. L’exemple d’un forum de lecteurs-consommateurs - Éric Sotto (Communiquer)
In this statement, we questioned the editorial practices and the new expertise in development in the public forum of discussion Booknode.com gathering the users-consumers talking about the digital book. Our cross-disciplinary approach is based on the theoretical setting of the interactionism, by borrowing the concepts of the daily interactions and verbal interactions analysis, by processing to a qualitative analysis of a digital corpus. We maintain that the forum of users-consumers constitutes a documentary area self-administered and self-regulated by a myriad of amateurs. The expression of an individual opinion translates into a pileup of detailed and commented feedback of consumption experiences. This breeding ground of daily micro-practices meet the co-innovative practices that favors a generation of spontaneous ideas exploitable by a community manager who turns into, in this socio-technical platform, in a discreet and distant facilitator intervening to initiate-urge on the conversation, as a silent and rigorous prospector exploiting the participants’ feedback on their experiences to detect innovative practices.